Epigenetic determinants of cardiovascular gene expression: vascular endothelium. (July 2016) - Man, Hon-Sum Jeffrey; Yan, Matthew S; Lee, John JY; Marsden, Philip A
The modern landscape of gene regulation involves interacting factors that ultimately lead to gene activation or repression. Epigenetic mechanisms provide a perspective of cellular phenotype as dynamically regulated and responsive to input. This perspective is supported by the generation of induced pluripotent stem cells from fully differentiated cell types. In vascular endothelial cells, evidence suggests that epigenetic mechanisms play a major role in the expression of endothelial cell-specific genes such as the endothelial nitric oxide synthase ( NOS3 /eNOS). These mechanisms are also important for eNOS expression in response to environmental stimuli such as hypoxia and shear stress. A newer paradigm in epigenetics, long noncoding RNAs offer a link between genetic variation, epigenetic regulation and disease. While the understanding of epigenetic mechanisms is early in its course, it is becoming clear that approaches to understanding the interaction of these factors and their inputs will be necessary to improve outcomes in cardiovascular disease.